TINJAUAN YURIDIS ACTE VAN DADING YANG DIBUAT DI HADAPAN NOTARIS DALAM PROSES PENYELESAIAN MEDIASI SENGKETA TANAH - , Arif Ramasiwi Gayuh Priambodo; , Dr. Tata Wijayanta, S.H, M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research aims to, 1. examine notaryâs authority in the making of acte van dading as requested by the disputed parties, 2. Examine the legal position of acte van dading on mediation process for land dispute settlement, and 3. to identify which factors become obstacles in the mediation process for land dispute settlement. The research is a normative empirical legal studies in which uses secondary and primary data acquired through library and field research. The secondary data was obtained through documentation method using document study instrument, while the primary data was obtained through interviews using the interview guide instrument, the interviews located in Kantor Wilayah Badan Pertanahan (BPN) Provinsi Jawa Barat, the interviewees was official at Kantor Wilayah BPN Provinsi Jawa Barat, the mediator assigned by BPN and the disputed parties. Data analysis was done qualitatively. The researchâs results that notary has the authority to make acte van dading made in his presence on mediation process for land dispute settlement. The disputed parties and the mediator found that acte van dading made by notary has a sufficient legal position although the act was not registered to the court, because the authentic deed made by notary has the ability to prove its own legitimacy (acta publica probant sese ipsa). The factors which become obstacles in the mediation process is 1. the lack of the professional mediator who understand the technical issues in land disputes, 2. the mediator assigned by BPN in mediating land disputes as requested by the disputed parties does not have the mediator certificate as a license to mediate, and 3. the issue of BPNâs neutrality in the dispute because it involves legal products made by BPN. The conclusion is notary has the authority to make acte van dading, it has sufficient legal standing and to provide certainty for the disputed parties but as limited as the position of an authentic deed, the main factors that become obstacles of the mediation is the lack of the proffesional mediator in the matter of land dispute, the mediator assigned by BPN does not have the mediator certificate as a license to mediate and the issue of BPNâs neutrality. Therefore recommended 1. BPN to cooperate with the notary to accelerate the land dispute windup, 2. acte van dading made by notary should be registered to the court according to the procedure in order to acquired the power to execute if only one of the disputed parties breach the agreement, and 3. BPN to improve its profesinalism and conduct education and training for mediator candidate to obtain certification of mediator.